Pelaksanaan Pembangunan Jalan Cisalatri Bandung - Susilo, Budi Hartanto; Imanuel, Ivan (Zenit, 2014)
Transportation infrastructure is available in Indonesia, yet it is not sufficient to meet the increasing demand. Construction of new infrastructure is needed to support the transportationsystem. The construction of Cisalatri Road and Bridge project is a construction of a new access road to Gelora Bandung Lautan Api Stadium from Rancanumpang Highway. The type of the constructed road pavement is a rigid pavement. The work includes excavation (using equipment), pile foundation,limestone embankment, geotextile, soil embankment, base course, lean concrete, and concrete pavement work. Based on the result of fatigue and erotion analysis, the concrete pavement thickness with an excess thickness of about 4 cm is eligible. The project has some delays due to change ofworkplan, large amount of rain, limited materials and human resources, as well as the availability of heavy equipment.Keywords: construction, access road, Gedebage